KEGIATAN PENGABDIAN MASYARAKAT: PELATIHAN PENYAJIAN LAPORAN KEUANGAN UNTUK UMKM DI KABUPATEN PINRANG - Rahman Pura; Sahidah Sahidah; Sutiati Sutiati; Eva Marin Sambo; Andi Sultati; Muzdalifah Muzdalifah; Ryan Putra Hafikar (Lembaga Penelitian, Publikasi dan Pengabdian Masyarakat ITB Nobel Indonesia, 2022)
The purpose of the activity is to improve understanding of bookkeeping management for Small and Medium Enterprises in Pinrang Regency. Methods of delivering material in the form of lectures. The lecture form is used by the speaker to convey the activity material, then proceed with simulation and discussion. Training activities provide benefits in increasing the ability and convenience in managing MSME finances